Analisis Pengaruh Upah Dan Insentif Terhadap Produktivitas Kerja Karyawan PT Artamas Kurnia Bekasi - Syarif, Mahmud; Hendy, Hendy (CV Warnak Johanna Nusantara, 2025)
- Technological developments cause competition. An organization is expected to have high productivity with good and quality (HR) in carrying out all its operations as a workforce. The wage level which is still very low will affect employee efforts to increase their productivity, but it is difficult to guarantee a wage increase if productivity is very low, so the author is interested in raising the problem with the title